2017
DOI: 10.1016/j.physletb.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A novel nuclear dependence of nucleon–nucleon short-range correlations

Abstract: A linear correlation is found between the magnitude of nucleon-nucleon short-range correlations and the nuclear binding energy per nucleon with pairing energy removed. By using this relation, the strengths of nucleon-nucleon short-range correlations of some unmeasured nuclei are predicted. Discussions on nucleonnucleon pairing energy and nucleon-nucleon short-range correlations are made. The found nuclear dependence of nucleon-nucleon short-range correlations may shed some lights on the short-range structure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The most important ones are the nuclear interaction energy and the Coulomb energy due to the Coulomb repulsion between the protons. According to Weizsäcker semiempirical mass formula (SEMF), the binding energy equation (Dai et al 2017;Heyde 2004) is written as,…”
Section: Methodsmentioning
confidence: 99%
“…The most important ones are the nuclear interaction energy and the Coulomb energy due to the Coulomb repulsion between the protons. According to Weizsäcker semiempirical mass formula (SEMF), the binding energy equation (Dai et al 2017;Heyde 2004) is written as,…”
Section: Methodsmentioning
confidence: 99%
“…1 are the R max -ν c (upper panel) and M max NS -Γ c (lower panel) correlations by using 87 phenomenological and 17 extra microscopic NS EOSs with and/or without considering hadron-quark phase transitions and hyperons by solving numerically the original TOV equations. The phenomenological EOSs are from three rather different classes of EOS models (Iida & Sato 1997): the covariant relativistic mean-field (RMF) models (Serot & Walecka 1986), the non-relativistic energy density functionals (EDF) of the Gogny-like type (Cai & Li 2022) as well as the conventional Skyrme-type (Vautherin & Brink 1972;Stone & Reinhard 2007;Zhang & Chen 2016). Within each EOS class, different EOS models are generated by perturbing the model coupling constants within their empirical uncertain ranges.…”
Section: Validations Of Ns Radius/mass Scalings By Solving the Origin...mentioning
confidence: 99%
“…In recent two years, the study of nuclear short-range correlations attracts much attention [1][2][3][4][5][6]. It has been shown that about 20% nucleons in nuclei are correlated [7][8][9].…”
mentioning
confidence: 99%